CDR 2020
DOI: 10.20517/cdr.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

PHGDH as a mechanism for resistance in metabolically-driven cancers

Abstract: At the forefront of cancer research is the rapidly evolving understanding of metabolic reprogramming within cancer cells. The expeditious adaptation to metabolic inhibition allows cells to evolve and acquire resistance to targeted treatments, which makes therapeutic exploitation complex but achievable. 3-phosphoglycerate dehydrogenase (PHGDH) is the rate-limiting enzyme of de novo serine biosynthesis and is highly expressed in a variety of cancers, including breast cancer, melanoma, and Ewing's sarcoma. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 104 publications
(138 reference statements)
1
27
0
Order By: Relevance
“…Upregulation of PHGDH has been observed in many cancers, including melanoma, breast cancer, leukemia and colorectal cancer ( Locasale et al, 2011 ) ( Fan et al, 2015 ) ( Polet et al, 2016 ) ( Jia et al, 2016 ) ( Zhao et al, 2020 ). This upregulation is thought to be linked to increased demands for folate and methionine cycle-related processes such as DNA synthesis, biomass production and epigenetic modifications ( Rathore et al, 2020 ). Targeting the folate cycle is a mainstay of treatment in several cancers, including OS, with MTX being one of the oldest and still most widely used chemotherapeutics ( Ghodke-Puranik et al, 2015 ).…”
Section: Mitochondria and Metabolic Reprogrammingmentioning
confidence: 99%
“…Upregulation of PHGDH has been observed in many cancers, including melanoma, breast cancer, leukemia and colorectal cancer ( Locasale et al, 2011 ) ( Fan et al, 2015 ) ( Polet et al, 2016 ) ( Jia et al, 2016 ) ( Zhao et al, 2020 ). This upregulation is thought to be linked to increased demands for folate and methionine cycle-related processes such as DNA synthesis, biomass production and epigenetic modifications ( Rathore et al, 2020 ). Targeting the folate cycle is a mainstay of treatment in several cancers, including OS, with MTX being one of the oldest and still most widely used chemotherapeutics ( Ghodke-Puranik et al, 2015 ).…”
Section: Mitochondria and Metabolic Reprogrammingmentioning
confidence: 99%
“…( 18 ) demonstrated that PHGDH is a major determinant of brain metastasis in multiple human cancer types and preclinical models and explored the possibility of PHGDH inhibitors for treating brain tumor metastasis. These findings suggest that targeting PHGDH provides a promising anticancer and drug resistance approach ( 19 ).…”
mentioning
confidence: 99%
“…Multiple efforts have identified targets of the EWS/FLI1 fusion that are involved in ES tumorigenesis, including TRIM8 [20] , H3K27ac , and RNA polymerase II genes [21] . Another approach to combating ESW-FLI1 oncoprotein expression involves targeting L1RAP and phosphoglycerate dehydrogenase (PHGDH), which augment cysteine [22] and serine [23] uptake, or inhibiting BTG [24] , which induces cell proliferation.…”
Section: Oncogenesis Of Sarcomasmentioning
confidence: 99%